Diamagnetic Susceptibility of a Confined Donor in a Quantum Dot with Different Confinements - Peter, A. J.; Ebenezar, J. (Journal of Scientific Research, 2009)
The binding energies of shallow hydrogenic impurity in a GaAs/GaAlAs quantum dot with spherical confinement, harmonic oscillator-like and rectangular well-like potentials are calculated as a function of dot radius using a variational procedure within the effective mass approximation. The calculations of the binding energy of the donor impurity as a function of the system geometry have been investigated. A comparison of the eigenstates of a hydrogenic impurity in all the confinements of dots is discussed in detail. Â We have computed and compared the susceptibility for a hydrogenic donor in a spherical confinement, harmonic oscillator-like and rectangular well-like potentials for a finite QD and observe a strong influence of the shape of confining potential and geometry of the dot on the susceptibility. Â Keywords: Quantum dot; Quantum well wire; Quantum well; Diamagnetic susceptibility; Donor impurity. Â Â© 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. Â DOI: 10.3329/jsr.v1i2.1184 Â Â Â